Female Labor Supply in the Context of Inflation - Niemi, Beth; Lloyd, Cynthia B. (American Economic Review, 1981)
Inflation has become, the 1970's, an important economic phenomenon that must be taken into account analyzing the determinants of labor supply trends. Traditional labor supply theory has focused on the overriding importance of real wage growth as a primary determinant of both the long-run secular decline hours of work and the postwar increase the labor force participation rate of married women. Within this context, any labor supply effects of price level changes have been subsumed under the overall effect of real wages. However, despite unusually rapid price increases as well as stagnation the growth of productivity and real wages the last decade, the growth women's labor force participation has continued and, if anything, accelerated the last decade. Thus it is clear that, today, factors other than real wage growth must lie behind this continuing upward trend. Inflation is well worth exploring as a possible independent influence on labor supply, because of both its growing visibility and the frequency with which one hears comments along the lines of in these inflationary times, a family needs two salaries to make ends meet. Our objective this paper is to explore the possible effects of inflation on women's labor supply trends. As a first step this direction, we present some empirical results, relating changes the labor force participation rates of women various age groups to inflation as well as other independent variables, covering the period 1956-77. Inflation clearly appears to have an effect on labor force participation rates above and beyond the effect it generates through reducing the real wage. By next examining the primary sources of women's labor force growth the last decade and their implications for long-run labor supply, we suggest the likely importance of inflationary expectations sustaining the long-term growth of women's labor supply, particularly the prime age group.